2018
DOI: 10.2147/ijn.s167035
|View full text |Cite
|
Sign up to set email alerts
|

Thermally induced self-agglomeration 3D scaffolds with BMP-2-loaded core–shell fibers for enhanced osteogenic differentiation of rat adipose-derived stem cells

Abstract: IntroductionScaffold structure plays a vital role in cell behaviors. Compared with two-dimensional structure, 3D scaffolds can mimic natural extracellular matrix (ECM) and promote cell–cell and cell–matrix interactions. The combination of osteoconductive scaffolds and osteoinductive growth factors is considered to have synergistic effects on bone regeneration.Materials and methodsIn this study, core–shell poly(lactide-co-glycolide) (PLGA)/polycaprolactone (PCL)–BMP-2 (PP–B) fibrous scaffolds were prepared thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…ALP was identified as a marker of early osteoblastic differentiation. 47,48 ALP staining and activity assays were performed on days 7 and 14 after transfections to test the osteogenic differentiation level of rBMSCs. The highest ALP staining intensity was found in the group treated with MSN_miR-26a@PEI-KALA, whereas negligible difference was observed among the other three groups ( Figure 7A).…”
Section: Alp Activity and Mineralization Evaluationmentioning
confidence: 99%
“…ALP was identified as a marker of early osteoblastic differentiation. 47,48 ALP staining and activity assays were performed on days 7 and 14 after transfections to test the osteogenic differentiation level of rBMSCs. The highest ALP staining intensity was found in the group treated with MSN_miR-26a@PEI-KALA, whereas negligible difference was observed among the other three groups ( Figure 7A).…”
Section: Alp Activity and Mineralization Evaluationmentioning
confidence: 99%
“…The results of this study suggest combination therapy using stem cells and BMP-2 with a three-dimensional approach. The combined approach of osteoconductive scaffolds and osteoinductive growth factors may have synergistic effects on osteogenesis ( 17 ). In a previous report, the application of a combined approach with bone marrow mesenchymal stem cells, BMP-2 and hydroxyapatite led to successful treatment of critical-sized defects in human beings ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…For the assays with more than 2 groups, it is necessary to perform ANOVA, considering non-normal distribution and unpaired samples. In a different approach, PLGA/PCL-BMP2 3D scaffolds were produced via TISA for bone regeneration [87]. The electrospun scaffolds were prepared as a core-shell structure, where the shell was a blend of PLGA and PCL, and the core consisted of BMP-2 with bovine serum albumin.…”
Section: Electrospinningmentioning
confidence: 99%
“…Scaffolds presented a sustained release of BMP-2 within all the time periods evaluated, along with improved rat adipose-derived stem cells (rADSCs) attachment, proliferation, and osteogenic differentiation. The authors concluded that 3D scaffolds with osteoinductive growth factors are potential candidates for reconstructing bone defects in bone tissue engineering and dental medicine applications [87]. Authors invested in a core-shell technology to produce the scaffolds; however, this is not obvious why, because the structures were used to obtain 3D scaffolds via TISA.…”
Section: Electrospinningmentioning
confidence: 99%